Adaptation of an Antarctic lichen to Martian niche conditions can occur within 34 days - de Vera, Jean Pierre Paul; Schulze-Makuch, D.; Khan, A.; Lorek, Andreas; Koncz, Alexander; Möhlmann, D.; Spohn, Tilman (Planetary and Space Science, 2013)
Stresses occurring on the Martian surface were simulated in a Mars Simulation Chamber (MSC) and included high UV fluxes (Zarnecki et al., 2002), low temperatures, low water activity, high atmospheric CO2 concentrations, and an atmospheric pressure of about 800 Pa (Kasting, 1991, Head et al., 2003). The lichen Pleopsidium chlorophanum is an extremophile that lives in very cold, dry, high-altitude habitats, which are Earth's best approximation of the Martian surface. Samples with P. chlorophanum were exposed uninterruptedly to simulated conditions of the unprotected Martian surface (i.e. 6344 kJm-2) and protected niche conditions (269 kJm-2) for 34 days. Under unprotected Martian surface conditions the fungal symbiont decreases its metabolic activity and it was unclear if the algal symbiont of the lichen was still actively photosynthesizing. However, under ―protected site― conditions, the entire lichen not only survived and remained photosynthetically active, it even adapted physiologically by increasing its photosynthetic activity over the 34 days.